Glial inflammatory signaling in manganese neurotoxicity - Moreno, Julie Ann, author; Tjalkens, Ronald B., advisor (Colorado State University. Libraries, 2009)
Degenerative movement disorders affecting the basal ganglia, including, Parkinson's (PD) and Huntington's diseases, are debilitating and currently incurable. Increased inflammatory gene expression in astrocytes promotes neuronal loss in these disorders, but the signaling mechanisms underlying this phenotype are not fully understood. In order to enhance understanding of this phenotype, the degenerative movement disorder, manganism, is a useful model, because patients suffering from excessive exposure to manganese (Mn) develop a neurodegenerative condition affecting the same brain region and with clinical features resembling PD. Recently, the potential effects of Mn on the developing brain have gained attention due to an increase in cognitive deficits with overexposure to Mn. Moreover, astrocytes are a known target of Mn, and reactive gliosis seems to precede neuronal injury. Mn toxicity enhances production of the inflammatory mediator nitric oxide (NO) in astrocytes by a mechanism involving NF-κB, the principal transcription factor responsible for expression of inducible nitric oxide synthase (NOS2). However, the role Mn toxicity plays in the developing brain along with the signaling mechanism(s) by which Mn enhances activation of NF-κB remains poorly understood in astrocytes. Therefore, in order to address the gap in knowledge I have characterized the role of glial cells in the promotion of neuronal damage in the developing and adult brain in a mouse model of Mn neurotoxicity, as well as the mechanism by which Mn enhances inflammatory activation of NF-κB dependent genes in astrocytes. First, it was identified that sGC relays signals to ERK and NF-κB, initiating NO signaling in astrocytes. Also it was determined that the glial inflammatory response leads to an age- and sex-dependent vulnerability of the basal ganglia which can be modulated by E2. This indicates that Mn toxicity in the developing brain results in locomotor deficits, reduction in normal dopaminergic neurotransmitter release, increased NOS2 expression in glial cells and neuronal injury. These findings are significant because once the mechanism of Mn-induced inflammatory activation of glial cells is understood, it will promote a better understanding of manganism and potentially other disorders of the basal ganglia.
Keywords: astrocytes; inflammatory signaling; manganese; neurotoxicity; nitric oxide; molecular biology; neurosciences; surgery